G Protein Coupled Receptors: understanding how our body responds to signals - Gonzales Gil, Patricia (2012)
This year's Nobel Prize in Chemistry was awarded to Americans Robert Lefkowitz and Brian Kobilka for their studies of G protein coupled receptors. These receptors are involved in cell-cell and long-distance signaling in our organisms. Moreover, they are so important for most physiological processes in human beings that practically half of our medications act through them. Studying these receptors at a molecular level is an extremely complex task but today, through the work of these two researchers, we have gained a better understanding of the mechanisms by which these receptors operate